Case Report: Laparoscopic appendectomy in a patient with congenital visceral heterotaxy and severe adhesions - Liu, Dake; Zhao, Xinying; Li, Lin; Liu, Weibo (Frontiers in Surgery, 2025)
BackgroundCongenital visceral heterotaxy (CVH) is a rare congenital anomaly characterized by the abnormal arrangement (malposition) of thoracic and abdominal organs. This condition can significantly complicate surgical planning and intraoperative management, particularly when a history of prior abdominal surgery is present and laparoscopic intervention is required. The limited literature on managing such cases underscores the necessity for meticulous preoperative planning and intraoperative adaptability.Case summaryA 42-year-old Chinese woman with congenital visceral heterotaxy and a history of cesarean section 11 years prior was admitted with acute suppurative appendicitis. Preoperative imaging, including ultrasound and CT, confirmed the diagnosis and revealed severe intra-abdominal adhesions. The patient underwent a laparoscopic appendectomy under general anesthesia. During the procedure, adhesions—likely stemming from the prior cesarean section—significantly impeded visualization and access to the appendix. Despite these challenges, the appendectomy was completed successfully without complications. The patient's postoperative recovery was uneventful, and she was discharged on the third postoperative day.ConclusionThis report highlights the successful management of a complex case involving a patient with both congenital visceral heterotaxy and severe intra-abdominal adhesions. It demonstrates that laparoscopic surgery is a feasible and safe option in such challenging scenarios, emphasizing the critical importance of meticulous preoperative planning, intraoperative adaptability, and a patient-tailored surgical approach. This case contributes to the sparse literature on laparoscopic surgery in patients with CVH and a history of abdominal surgery, offering valuable insights for surgeons facing similar complex presentations.